2021
DOI: 10.21873/cgp.20299
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Instability of Trimethylation of Histone H3 Lysine Increases With Degree of Malignancy and Methionine Addiction

Abstract: Background/Aim: Methionine addiction is a fundamental and general hallmark of cancer, termed the Hoffman effect. Methionine addiction is due to excessive use of and dependence on methionine by cancer cells. In the 12 This article is freely accessible online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 27 publications
4
33
0
Order By: Relevance
“…The present study along with our recent study (Yamamoto et al, 2020a), suggest that malignant cells require histone H3 lysine hypermethylation to grow in vitro and to form tumors and metastasis in vivo. Our recent results have demonstrated that high malignancy variants of methionine-addicted parental cancer cells, become even more methionine-addicted, form large tumors, and increase the amount of trimethylated histone H3 lysine marks (Yamamoto et al, 2022), further emphasizing the close association of the three phenomena. The present study thus shows that histone H3 pan-overmethylated lysine marks explain, at least in part, the fate of an important set of methyl-groups in cancer cells and why cancer cells are methionine addicted, but not normal cells or methionine-independent revertant cells.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The present study along with our recent study (Yamamoto et al, 2020a), suggest that malignant cells require histone H3 lysine hypermethylation to grow in vitro and to form tumors and metastasis in vivo. Our recent results have demonstrated that high malignancy variants of methionine-addicted parental cancer cells, become even more methionine-addicted, form large tumors, and increase the amount of trimethylated histone H3 lysine marks (Yamamoto et al, 2022), further emphasizing the close association of the three phenomena. The present study thus shows that histone H3 pan-overmethylated lysine marks explain, at least in part, the fate of an important set of methyl-groups in cancer cells and why cancer cells are methionine addicted, but not normal cells or methionine-independent revertant cells.…”
Section: Discussionmentioning
confidence: 81%
“…Methionine addiction is a fundamental and general hallmark of cancer and is known the Hoffman effect (Coalson et al, 1982;Hoffman and Erbe, 1976;Kaiser, 2020;Stern et al, 1983 and is an area of current intense interest (Gao et al, 2019;Wang et al, 2019;Yamamoto et al, 2020aYamamoto et al, , 2021Yamamoto et al, , 2022. Methionine addiction is characterized by a requirement for exogenous methionine for growth by cancer cells even though the methionine-addicted cancer cells synthesize normal or excess amounts of methionine (Coalson et al, 1982;Hoffman and Erbe, 1976;Stern et al, 1983;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methionine addiction is a fundamental and general hallmark of cancer cells (5-7) (21)(22)(23). We previously showed that even though cancer cells can synthesize methionine from homocysteine to a similar or greater extent than normal cells, they require a large amount of exogenous methionine due to excess transmethylation reactions (9)(10)(11)24). Gao et al reported that methionine restriction enhanced the therapeutic response in RAS-driven colorectal cancer and soft-tissue sarcoma in patient-derived xenograft models (PDX) (25), confirming results we found more than 25 years earlier (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%